Enhancing Fourth-Grade Sciences and Social Sciences Learning Outcomes Through STAD Cooperative Learning with Audio-Visual Media - Sufyan, Mohammad; Misnah, Misnah; Wilade, Surahman; Firmansyah, Arif; Putriwanti, Putriwanti (Papanda Publisher, 2025)
Traditional teacher-centered instruction in elementary Sciences and Social Sciences (IPAS) education creates passive learning environments that limit student engagement and comprehension. This classroom action research investigated the effectiveness of integrating Student Teams Achievement Division (STAD) cooperative learning with audiovisual media to improve fourth-grade learning outcomes at SDN 8 Mamboro. The study employed Kemmis and McTaggart's cyclical model across two implementation cycles, utilizing total sampling of 29 students during the 2024/2025 academic year. Data collection incorporated validated achievement tests, structured observation sheets, and comprehensive documentation to evaluate both quantitative learning outcomes and qualitative behavioral changes. Mixed-methods analysis examined classical mastery percentages, absorption rates, and observational effectiveness scores across intervention cycles. Results demonstrated substantial improvements from Cycle I to Cycle II: student mastery completion increased from 43.47% to 100%, classical absorption improved from 60.43% to 83.57%, teacher effectiveness enhanced from 82.14% to 95.23%, and student participation rose from 75% to 97.36%. The integration of structured cooperative learning with multimedia instruction successfully eliminated academic failure while fostering collaborative competencies and active engagement. These findings provide empirical evidence supporting cooperative learning theory while demonstrating practical applications for contemporary elementary education. The study contributes a replicable framework for educators seeking to enhance student-centered instruction through systematic integration of collaborative pedagogies and educational technology, though broader implementation requires investigation across diverse educational contexts.